The Victimizer as Subject of Pain. the Figurability of the Perpetrator in the Chilean Documentary Film "El Mocito" 2011 - Faure-Bascur, E (UNIV PAIS VASCO, 2021)
This article analyzes the figurability of the perpetrator in the documentary film "El Mocito" by Marcela Said and Jean De Certeau (2011). The theoretical-methodological proposal of L. Zylberman has been followed for the analysis of the representations of the perpetrators in the documentary, based on the observation of the forms and modalities under which these actors appear. First of all, the narrative scope of the film is analyzed, corresponding to the form, to later delve into the modality of appearance of the victimizer, by highlighting some aspects of the development of this character. It is concluded that the film elaborates a representation of the perpetrator that, by being centered in the extreme vulnerability of the subject, eludes the discussion about his responsibility, by offering a reductionist portrait of the protagonist (Jorgelino Vergara, "El Mocito"), focused on the havoc that the regime has produced in his life. This ambiguity regarding the question of responsibility is based on an emptying of the character s subjectivity, of his possible ideology and agency, and in the elaboration of a narrative arc in which confessional religious senses predominate.